The Effect of Training and Education on Strengthening LPPKS Principals on the Dimensions of Planning, Management, Supervision on the Managerial Competence of Islamic Kindergarten Principals in Wonocolo District, Surabaya City.: Pengaruh Diklat Penguatan Kepala Sekolah LPPKS Terhadap Dimensi Perencanaan, Pengelolaan, Pengawasan Pada Kompetensi Manajerial Kepala TK Islam di Kecamatan Wonocolo Kota Surabaya. - Wahyu Nurdiyati; Budi Haryanto (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study was to examine the effect of Principal Strengthening Education and Training on the dimensions of planning, management and supervision on managerial competence of Islamic Kindergarten principals in Wonocolo sub-district, Surabaya. This analysis uses quantitative methods. The sample of this study was the principal of an Islamic kindergarten in the Wonocolo sub-district of Surabaya city who had attended the training for strengthening the principal of the city of Surabaya in 2019. The data was collected through a questionnaire. The statistical test method is nonparametric analysis using the boots rapping method. The results of the research on the effect of training and education on the strengthening of school principals on managerial competence of principals in planning dimensions are 0.034. In the management dimension, the significance value is 0.025 and the supervision dimension produces a significance value of 0.037. The overall dimension of managerial competence, the resulting significance value is smaller than a significant alpha of 5% or 0.05. This means that there is a significant effect of training and education on the strengthening of principals on the managerial competence of principals in the dimensions of planning, management and supervision.